Microfluidics: Microfluidic Single‐Cell Analysis with Affinity Beads (Small 22/2015). Issue 22 (June 2015) - Werner, Michael; Palankar, Raghavendra; Arm, Loïc; Hovius, Ruud; Vogel, Horst
<x xml:space="preserve">Abstract</x> To investigate functional heterogeneity between individuals in a cell population, affinity beads are transferred into living mammalian cells by H. Vogel and co‐workers. On page 2607, beads coated with specific capture agents efficiently bind and up‐concentrate cytosolic target proteins on their surface. For single‐cell analysis, an optically trapped bead with bound target proteins is extracted from its host cell in a microfluidic device. Compared to classical chemical cytometry, this method has the potential to reach high analytical sensitivity and throughput for single‐cell analysis in many biomedical fields.